The Effectiveness of Various Attractants in Attracting Aedes Sp Mosquitoes as a Strategy to Control Dengue Fever Cases : A Literature Review - Subekhi, Tatag Fajar; Wahyuningsih, Nur Endah; Raharjo, Mursid (Jurnal Riset Kesehatan, 2025)
Dengue Hemorrhagic Fever (DHF) remains one of the major public health challenges, particularly in tropical countries such as Indonesia. Conventional vector control strategies, such as fogging and mosquito breeding site eradication, have encountered significant obstacles, including insecticide resistance and limited long-term effectiveness. This study aims to examine the effectiveness of various natural attractants as an alternative approach to attracting Aedes mosquitoes through a Systematic Literature Review (SLR) of 24 published articles from 2020 to 2025. The attractants analyzed include fermented rice straw water, coconut husks, fermented sugar solutions, as well as grass-based and plant semiochemical attractants. The review results indicate that fermented rice straw water is the most effective attractant for Aedes mosquitoes, especially for gravid females, due to its organic compounds produced during fermentation, such as ammonia and volatile acids. Sugar solutions, particularly in the form of Attractive Toxic Sugar Baits (ATSB), also show high effectiveness in both attracting and killing mosquitoes. In contrast, coconut husk attractants tend to be less effective and their performance varies depending on environmental conditions. Grass-based attractants such as Megathyrsus maximus also show potential but still require broader field validation. Based on a literature review of 24 studies, it can be concluded that straw-soaked water is the most effective attractant. This is effective with 3-7 days of fermentation at warm temperatures and in dark containers. Environmental health implications include its suitability as a low-cost lure and kill. Integrating natural attractants with attract-and-kill approaches such as ATSB can enhance the effectiveness of dengue control programs in a sustainable manner, especially in resource-limited settings.